2007
DOI: 10.1044/1092-4388(2007/075)
|View full text |Cite
|
Sign up to set email alerts
|

Relations Among Socioeconomic Status, Age, and Predictors of Phonological Awareness

Abstract: The current study provides further support for both the phonological distinctness hypothesis and the lexical restructuring model. Additionally, this study provides novel information regarding the role that age plays in the prediction models. Specifically, the effects of SES and speech sound accuracy on phonological awareness were amplified by age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
61
0
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 41 publications
(48 reference statements)
6
61
0
12
Order By: Relevance
“…However, it is possible to verify that their language development was less than expected for the age. These changes may be related to various factors, among them deficient opportunities for learning caused by poor stimulatory environments due to the socioeconomic level, as demonstrated by Engel et al (2008) and McDowell et al (2007).…”
Section: Instrumentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is possible to verify that their language development was less than expected for the age. These changes may be related to various factors, among them deficient opportunities for learning caused by poor stimulatory environments due to the socioeconomic level, as demonstrated by Engel et al (2008) and McDowell et al (2007).…”
Section: Instrumentsmentioning
confidence: 99%
“…Evolutive differences in the phonological awareness tasks have not been fully elucidated, however, some evidence indicates reciprocal influences between phonological awareness abilities and learning to read and write, that is, as phonological awareness is a prerequisite for learning to read and write (McDowell, Lonigan, & Goldstein, 2007;Mota & Guimarães, 2011;Peeters, Verhoeven, de Moor, & van Balkom, 2009), the phonological awareness abilities can also be improved and expanded by exposure of the individual to being taught to read and write (Bernardino Junior, Freitas, Souza, Maranhe, & Bandini, 2006;Freitas, 2008).…”
mentioning
confidence: 99%
“…They found that children with more atypical errors experience inferior performance in PA skills (12,15,16). The literature has also shown that there is a positive relation between speech sound accuracy measured by percent consonant correct (PCC) and PA skills (17). Although the literature suggests there is a relationship between PD and PA, it has also been shown that children with SSD do not exhibit PA problems (18,19).…”
Section: Introductionmentioning
confidence: 92%
“…Firstly, although socioeconomic status (SES) is important when studying children with SSD (17), no valid and reliable instrument exists to measure socioeconomic status in Iran. In order to diminish SES' effect, we tried to select children based on residential area and mother's education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation